2019
DOI: 10.4049/jimmunol.1801519
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Chemokine Receptor Inhibition in Treating IL-36α–Induced Psoriasiform Inflammation

Abstract: Several types of psoriasiform dermatitis are associated with increased IL-36 cytokine activity in the skin. A rare, but severe, psoriasis-like disorder, generalized pustular psoriasis (GPP), is linked to loss-of-function mutations in the gene encoding IL-36RA, an important negative regulator of IL-36 signaling. To understand the effects of IL-36 dysregulation in a mouse model, we studied skin inflammation induced by intradermal injections of preactivated IL-36α. We found the immune cells infiltrating IL-36α–in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…Previous studies revealed an important contribution of keratinocyte-derived CXCL1 and CXCL2 to the development of psoriasis, as these chemokines trigger the infiltration of neutrophils into the skin (30). In agreement, blocking of the CXCR2 receptor using a small-molecule antagonist efficiently blocked IL-36-driven skin inflammation (31). Similarly, we found that neutrophil and macrophage especially infiltration was absent in IMQ-or IL-36treated K14-Cre Nfkbiz-KO mice, along with a lack of expression of Cxcl1, Cxcl2, or Cxcl5.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies revealed an important contribution of keratinocyte-derived CXCL1 and CXCL2 to the development of psoriasis, as these chemokines trigger the infiltration of neutrophils into the skin (30). In agreement, blocking of the CXCR2 receptor using a small-molecule antagonist efficiently blocked IL-36-driven skin inflammation (31). Similarly, we found that neutrophil and macrophage especially infiltration was absent in IMQ-or IL-36treated K14-Cre Nfkbiz-KO mice, along with a lack of expression of Cxcl1, Cxcl2, or Cxcl5.…”
Section: Discussionsupporting
confidence: 67%
“…Preclinical studies have revealed that the humanized anti-CCR6 antibody efficiently inhibits the cutaneous infiltration of CCR6 + T cells in human and murine models [205,206]. The development of small molecule inhibitors against CCR6 is also ongoing [207,208]. Targeting the CCL20/CCR6 axis may be a potential therapeutic strategy for the treatment of psoriasis.…”
Section: Il-17a and Cyto/chemokines In Keratinocytesmentioning
confidence: 99%
“…In addition, preclinical study reveals that humanized anti‐CCR6 antibody efficiently inhibits the imiquimod‐induced psoriasiform dermatitis in human CCR6 ‐transgenic/mouse Ccr6 ‐deficient mice . Development of small molecule inhibitors against CCR6 is also ongoing . CCX624 is a potent antagonist for CCR6 and CXCR2 .…”
Section: The Ccl20/ccr6 Axis As Target For the Treatment Of Psoriasismentioning
confidence: 99%
“…75 Development of small molecule inhibitors against CCR6 is also ongoing. 76,77 CCX624 is a potent antagonist for CCR6 and CXCR2. 77 Administration of CCX624 significantly alleviates the imiquimod-induced and IL-36α-induced murine psoriasiform inflammation by inhibiting intralesional infiltration of CCR6+ T cells and dendritic cells as well as CXCR2+ neutrophils.…”
Section: Target For the Treatment Of Psoriasismentioning
confidence: 99%
See 1 more Smart Citation